Cost Estimation and Project Completion Time with Earned Value Analysis Approach on Waru-Buduran Frontage Road Project In Sidoarjo - Suparno Suparno; Hanie Teki Tjendani; Budi Witjaksana (Al-Makki Publisher, 2025)
The construction project of the Frontage Road Waru-Buduran in Sidoarjo has faced significant delays, highlighting the critical challenges in maintaining project efficiency. This study aims to analyze the cost and schedule estimates for the remaining work, as well as the total project completion using the Earned Value Analysis (EVA) method. The analysis results reveal a progress deviation of -9.911% by week 14 out of the total planned 21 weeks, indicating substantial schedule delays. Final completion estimates indicate a delay of 16.5 days and cost efficiency of IDR 1,246,797,954.06 (3.8%), demonstrating effective cost management despite schedule setbacks. EVA has proven effective in integrating cost and schedule performance indicators, such as Schedule Performance Index (SPI) and Cost Performance Index (CPI), to provide a comprehensive evaluation of project health. The findings emphasize the importance of early identification of deviations through EVA to implement corrective strategies, such as resource reallocation, schedule adjustments, and improved stakeholder coordination. The application of EVA enables project managers to predict potential risks, mitigate delays, and optimize resource utilization to achieve project objectives. This study provides valuable insights for project management practices, offering practical guidelines for addressing the complexities of construction projects. By utilizing EVA, project managers can ensure better decision-making, improve time and cost efficiency, and minimize conflicts arising from deviations in project execution. The findings serve as a reference for adopting EVA as a standard method in construction management to enhance overall project performance and ensure timely completion within budgetary constraints.